Apoptotic Diminution of Immature Single and Double Positive Thymocyte Subpopulations Contributes to Thymus Involution During Murine Polymicrobial Sepsis. Issue 2 (August 2017) - Netzer, Christoph; Knape, Tilo; Kuchler, Laura; Weigert, Andreas; Zacharowski, Kai; Pfeilschifter, Waltraud; Sempowski, Gregory; Parnham, Michael J.; Brüne, Bernhard; von Knethen, Andreas
Abstract : ABSTRACT: To generate and maintain functional T-cell receptor diversity, thymocyte development is tightly organized. Errors in this process may have dramatic consequences, provoking, for example, autoimmune diseases. Probably for this reason, the thymus reacts to septic stress with involution, decreasing the numbers of thymocytes. Because it is still unclear which thymocyte subpopulation contributes to thymus involution and whether thymocyte emigration is altered, we were interested to clarify this question in detail. Here, we show, using the cecal ligation and puncture (CLP) mouse model of polymicrobial sepsis, that predominantly immature thymocytes are reduced. The number of immature single positive thymocytes was most marked diminished (CLP: 6.54 × 10 4  ± 3.79 × 10 4 vs. sham: 4.54 × 10 5  ± 7.66 × 10 4  cells/thymus [24 h], CLP: 2.60 × 10 2  ± 2.14 × 10 2 vs. sham: 2.17 × 10 5  ± 1.90 × 10 4  cells/thymus [48 h]), and was consequently associated with the highest rate of apoptosis (8.4 [CLP] vs. 2.2% [sham]), the reduction in double positive thymocytes being associated with a smaller apoptotic response (number, CLP: 2.33 × 10 6  ± 1.38 × 10 6 vs. sham: 1.07 × 10 7  ± 2.72 × 10 6  cells/thymus [24 h], CLP: 2.34 × 10 3  ± 9.08 × 10 2 vs. sham: 3.5 × 10 6  ± 9.62 × 10 5  cells/thymus [48 h]; apoptosis: 2.5% [CLP] vs. 0.7% [sham]). Analysis of T-cell receptor excision circles revealed that the emigration of mature thymocytes was not inhibited. Real-time qPCR analysis revealed upregulation of pro-apoptotic Bim expression and suggested interference between Notch receptor expression on thymocytes and the respective ligands on thymic stromal cells during CLP-dependent sepsis, which might be responsible for the altered thymocyte viability in CLP-dependent sepsis. Abstract : Supplemental Digital Content is available in the text